The use of high resolution melting analysis of ITS-1 for rapid differentiation of parasitic nematodes Haemonchus contortus and Ashworthius sidemi - Skorpikova, Lucie; Reslova, Nikol; Magdalek, Jan; Vadlejch, Jaroslav; Kasny, Martin (Scientific reports, 2020)
Among gastrointestinal nematodes, haematophagous strongylids Haemonchus contortus and Ashworthius sidemi belong to the most pathogenic parasites of both domestic and wild ruminants. Correct identification of parasitic taxa is of crucial importance in many areas of parasite research, including monitoring of occurrence, epidemiological studies, or testing of effectiveness of therapy. In this study, we identified H. contortus and A. sidemi in a broad range of ruminant hosts that occur in the Czech Republic using morphological/morphometric and molecular approaches. As an advanced molecular method, we employed qPCR followed by High Resolution Melting analysis, specifically targeting the internal transcribed spacer 1 (ITS-1) sequence to distinguish the two nematode species. We demonstrate that High Resolution Melting curves allow for taxonomic affiliation, making it a convenient, rapid, and reliable identification tool.
Keywords: mezerníky ribozomální DNA; DNA helmintů; polymorfismus genetický; Female; DNA, Helminth; zvířata; Haemonchus; Polymorphism, Genetic; reprodukovatelnost výsledků; přežvýkavci; ženské pohlaví; Male; Reproducibility of Results; Czech Republic; Real-Time Polymerase Chain Reaction; Animals; Česká republika; mužské pohlaví; Trichostrongyloidea; DNA, Ribosomal Spacer; Ruminants; kvantitativní polymerázová řetězová reakce